Neurodegenerative diseases : neurobiology, pathogenesis and therapeutics - Beal, M. Flint; Lang, Anthony E; Ludolph, Albert (Cambridge University Press, 2005)
Neurodegenerative diseases are major contributors to disability and disease, with Alzheimer\'s and Parkinson\'s diseases the most prevalent. This major reference reviews the rapidly advancing knowledge of pathogenesis and treatment of neurodegenerative diseases in the context of a comprehensive survey of each disease and its clinical features. The editors and contributors are among the leading experts in the field internationally. Covering basic science, diagnostic tools and therapeutic approaches, the book focuses on all aspects of neurodegenerative disease, including the normal aging process. The dementias, prion diseases, Parkinson\'s disease and atypical parkinsonisms, neurodegenerative ataxias, motor neuron diseases, degenerative diseases with chorea, iron and copper disorders, and mitochondrial diseases, are all methodically presented and discussed, with extensive illustrations. In each case the underlying genetics, neuropathological and clinical issues are fully reviewed, making this the most complete as well as the most authoritative reference available to clinicians and neuroscientists.
Keywords: Dementia; demence; Huntingtonova nemoc; Alzheimerova nemoc; Parkinsonova nemoc; Huntington Disease; Alzheimer Disease; Parkinson Disease; neurologie